13/2x-5=5x-17

Simple and best practice solution for 13/2x-5=5x-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13/2x-5=5x-17 equation:



13/2x-5=5x-17
We move all terms to the left:
13/2x-5-(5x-17)=0
Domain of the equation: 2x!=0
x!=0/2
x!=0
x∈R
We get rid of parentheses
13/2x-5x+17-5=0
We multiply all the terms by the denominator
-5x*2x+17*2x-5*2x+13=0
Wy multiply elements
-10x^2+34x-10x+13=0
We add all the numbers together, and all the variables
-10x^2+24x+13=0
a = -10; b = 24; c = +13;
Δ = b2-4ac
Δ = 242-4·(-10)·13
Δ = 1096
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1096}=\sqrt{4*274}=\sqrt{4}*\sqrt{274}=2\sqrt{274}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(24)-2\sqrt{274}}{2*-10}=\frac{-24-2\sqrt{274}}{-20} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(24)+2\sqrt{274}}{2*-10}=\frac{-24+2\sqrt{274}}{-20} $

See similar equations:

| 3/10(x-3)=6 | | 15x-2=65 | | 15x-2=65° | | 10x+2=15x-13 | | -8c+10=0 | | 3c=14=28 | | 11x-1=9x+3 | | 15x-2=15x−2=10x+23 | | x+25=1+4x | | --8c+10=0 | | 3(5-2x)=9x2+9 | | 69x-2=67x+2 | | 45=6d=-45 | | S-1.7x=5 | | 4h−10=2 | | 3m+5(1.75)=11 | | 4b+7=0 | | 20x-4=14x+20 | | 4(j-2)+(j-1)=17 | | 2(4x+3)=10x2 | | -3w+12=-9w-36 | | 16b-8=4b-1 | | 3(6x-4)+4x=36-2x | | 12t+4t-12t-3t+4t+1=11 | | 2x-1=5x+18 | | 743749969x+93673647x*837^94/83787x=1 | | 12+10x=60+6x | | 15x=4x+4 | | 5(3x-6)+10=-9x+24x-40 | | 71/2-f=3/14 | | 1+5n=-15+3n | | 10x-4(1x-5)=6x-15-5 |

Equations solver categories